Isolation and characterization of lactic acid bacteria from "ting" in the Northern Province of South Africa - Cloete, T.E. (Thomas Eugene), 1958- (University of Pretoria, 2013)
Dissertation (MSc (Microbiology))--University of Pretoria, 2007.